Trends for the Segregation Practices of International Students: A Review of Higher Education in Turkey - Tugba Hosgorur; İlker Aysel (Educational Process: International Journal)
Background/purpose - This study aims to explain international student mobility within Turkish higher education in terms of the push-pull factors that affect students’ choices to attend Turkey based on international students studying at a provincial university in Mugla, Turkey.